External Ventricular Drainage Infections: Experience From a Tertiary Care Center in Nepal (Nepal Journal of Neuroscience, 2016)
External Ventricular Drainage (EVD) related infection is one of the most dreaded infections in neurosurgical practice. The primary aim of this study was to assess the incidence of EVD infections in our hospital. In addition, we have made an attempt to evaluate the indication for EVD placement, influence of total drainage time in the risk of catheter infection, the most common bacterial spectra in cerebrospinal fluid (CSF) culture, and their antibiotic sensitivity pattern. This is a retrospective study of all patients who underwent EVD placement over a period of two years.Out of 60 patients who underwent EVD placement, 52 met the inclusion criteria for analysis. The ventricular catheters were in place from 1 to 23 days. Overall shunt infection rate was 36.5%. CSF cell count significantly correlated with the occurrence of a positive CSF culture (unpaired t test, p